Case-control study of severe pre-eclampsia of early onset. Issue 6392 (27th August 1983) - Moore, M P; Redman, C W
Abstract : Twenty four women with severe pre-eclampsia diagnosed before 34 weeks' gestation were compared with 48 randomly selected controls matched for age and parity. Subjects were studied in the puerperium using a questionnaire, clinical examination, and review of case records. A history of infertility, headaches (particularly migraine), pre-eclampsia in a previous pregnancy, or a raised serum alpha-fetoprotein concentration at the time of screening for neural tube defect in the index pregnancy were all identified as significant risk factors in the pre-eclamptic women. Maternal age, a history of chronic hypertension or renal disease, or excessive maternal weight were not significantly associated with pre-eclampsia. Almost all the infants of pre-eclamptic women showed retarded growth: 18 were below the 10th centile and only one weighed more than the 25th centile. Four babies died. These observations indicate that pre-eclampsia of early onset may differ from the late onset disease not only in its very high perinatal morbidity and mortality but in its distinctive maternal risk factors.